MOOC Development in Basic Natural Sciences as a Distance Learning Solution - Puspitasari, Yulia Dewi; Susdarwati, Susdarwati (UIN Fatmawati Sukarno Bengkulu, 2021)
The Covid-19 pandemic that occurred massively in Indonesia had an impact on distance / online learningthat must be done to reduce physical interaction between lecturers and students. Distance learning thathas been done is still one-way communication. Development of the Massive Open Online Course(MOOC) as a learning platform that can support distance learning. The purpose of this research is todevelop MOOCs as support for distance learning, to determine the quality of the MOOC, and the level ofMOOC satisfaction. The research method used is the ADDIE development model with phase analysis,design, development, implementation, dan evaluation. The results of the research at each stage are:analysis stage needs analysis and problem analysis on the need for distance learning solutions with activetwo-way communication. The design stage made a MOOC design with RPS, materials, videos, enrichmentquestions, and quizzes at every meeting. The development stage develops each menu stage in the MOOCfrom the expected competencies to the quiz. The implementation stage, validation of experts, andvalidation of small groups of students. The evaluation stage evaluates MOOCs both in language, layout,content, and user satisfaction. The conclusion of the study is that MOOC was developed with the stagesof analysis, design, development, implementation, and evaluation (ADDIE). The MOOC quality from thevalidation results obtained an average of 80,8 in the good category. The results of the user satisfactionlevel of MOOC Basic Natural Sciences were 78% with a good category.